Analysis of Fiber Orientation on the Bending Strength of Aluminium-Carbon Fiber FML Composites - Audyna Naomi, Irena; Yasa Utama, Firman (Fakultas Teknik Universitas Negeri Surabaya, 2025)
One such innovation is the application of composite materials as subtitutes for conventional metals. However, pure composites exhibit poor resistance to shock loads, leading to the development of Fiber Metal Laminates (FMLs), which combine carbon fiber and aluminium sheets. This research investigates the flexural behavior of carbon fiber-reinforced FMLs with varying fiber orientations (0°, 45°, dan 90°). The study employed a quantitative approach using an experimental method to evaluate the mechanical response under bending conditions. The laminates were manufactured using the vacuum infusion process, with epoxy resin as the matrix and aluminium as laminates and core. Bending tests were conducted in accordance with ASTM D790, using a Tarno Grocki universal testing machine. The results were evaluated based on maximum flexural strenght. The results showed significant differences in bending strenght based on fiber orientation. The highest bending strenght was recorded at 0° (111.43 MPa), followed by 45° (90.92 MPa), and 90° (69.87 MPa). This research may serve as a reference for futher development of FML composites for automotive body aplications.